Essential Guide to Manuscript Writing for Academic Dummies: An Editor’s Perspective - Syed Sameer Aga; Saniya Nissar (Biochemistry Research International)
Writing an effective manuscript is one of the pivotal steps in the successful closure of the research project, and getting it published in a peer-reviewed and indexed journal adds to the academic profile of a researcher. Writing and publishing a scientific paper is a tough task that researchers and academicians must endure in staying relevant in the field. Success in translating the benchworks into the scientific content, which is effectively communicated within the scientific field, is used in evaluating the researcher in the current academic world. Writing is a highly time-consuming and skill-oriented process that requires familiarity with the numerous publishing steps, formatting rules, and ethical guidelines currently in vogue in the publishing industry. In this review, we have attempted to include the essential information that novice authors in their early careers need to possess, to be able to write a decent first scientific manuscript ready for submission in the journal of choice. This review is unique in providing essential guidance in a simple point-wise manner in conjunction with easy-to-understand illustrations to familiarize novice researchers with the anatomy of a basic scientific manuscript.